Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Tracing arsenic and antimony in mining-impacted environments: New insights from antimony isotopes - Colin Ferrari; Kevin B. White; Carol J. Ptacek; David W. Blowes (Chemical Geology, 2026)

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Microplastic consumption elevates fish oxidative stress but does not affect predator-driven mortality - Amelia M. Mannering; David J. Burritt; Valeriya Komyakova; Maud C.O. Ferrari; George Vamvounis; Alexandra M. Gulizia; Adam Staples; Mark I. McCormick; Bridie J.M. Allan (Science of The Total Environment, 2025)

Skull roof anatomy of the Early Jurassic (Toarcian) acipenseriform †Gyrosteus mirabilis Woodward ex Agassiz, from Yorkshire, England, elucidates diversity of †Chondrosteidae - Samuel L.A. Cooper; Megan Jacobs; Lucrezia Ferrari; David M. Martill (Proceedings of the Geologists' Association, 2025)

A reassessment of the history of the temporal resolution of rainfall data at the global scale - Renato Morbidelli; Alessia Flammini; Odinakachukwu Echeta; Raffaele Albano; Gabriel Anzolin; David Zumr; Wafae Badi; Nicola Berni; Miriam Bertola; José María Bodoque; Theo Brandsma; Arianna Cauteruccio; et al. (Journal of Hydrology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Combining measurements and modelling to reveal long-term effects of nitrogen fertilizer application timing on N2O emissions in corn - Jongwon Kang; Pedro Vitor Ferrari Machado; David Hooker; Brian Grant; Ward Smith; Claudia Wagner-Riddle; Joshua Nasielski (Field Crops Research, 2025)

Environmental DNA Metabarcoding of Cephalopod Diversity in the Tyrrhenian Deep Sea - Martina La Torre; Alex Cussigh; Valentina Crobe; Martina Spiga; Alice Ferrari; Alessia Cariani; Federica Piattoni; Federica Costantini; Silvia Franzellitti; Alberto Pallavicini; David Stanković; Sergio Stefanni (Journal of Marine Science and Engineering, 2024)
The deep sea, the largest biome on Earth, is the least explored and understood. This lack of knowledge hampers our ability to understand and protect this important environment. In this study, water and sediment samples were collected at different depths in the central Mediterranean (224–780 m), specifically, within the Dohrn Canyon and the Palinuro Seamount, to investigate the diversity of cephalopods and establish a baseline knowledge of their distribution in these sites to preserve their habitats and estimate the impacts of human-driven environmental changes. Key taxa identified included Heteroteuthis sp., Loligo sp., and Histioteuthis sp., which were the most abundant across all sampling stations. A low overlap in species detection was observed between water and sediment samples, confirming previous findings that the typology of environmental matrices used in eDNA metabarcoding has a significant impact on the organisms detected and, therefore, the integrated use of different matrices to better represent local biodiversity is recommended. Furthermore, this study highlights the limitations posed by gaps in reference databases, particularly for deep-sea organisms, and addresses these by emphasising the need for improved multi-marker approaches and expanded reference databases to enhance the accuracy of eDNA-based biodiversity assessment.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Thermal modeling of the lunar South Pole: Application to the PROSPECT landing site - Michelangelo Formisano; Maria Cristina De Sanctis; Sarah Boazman; Alessandro Frigeri; David Heather; Gianfranco Magni; Matteo Teodori; Simone De Angelis; Marco Ferrari (Planetary and Space Science, 2024)

Evaluation of minimally invasive estrus synchronization protocols in brown brocket deer (Subulo gouazoubira) - Bianca Ferrari; David Javier Galindo; Lindsay Unno Gimenes; José Maurício Barbanti Duarte (Animal Reproduction Science, 2023)

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

CHIPS: an Extensible Toolbox for Cellular and Hemodynamic Two-Photon Image Analysis - Matthew J. P. Barrett; Kim David Ferrari; Jillian L. Stobart; Martin Holub; Bruno Weber (Neuroinformatics, 2018)

Targeted re‐sequencing confirms the importance of chemosensory genes in aphid host race differentiation - Isobel Eyres; Ludovic Duvaux; Karim Gharbi; Rachel Tucker; David Hopkins; Jean‐Christophe Simon; Julia Ferrari; Carole M. Smadja; Roger K. Butlin (Molecular Ecology, 2017)
Host‐associated races of phytophagous insects provide a model for understanding how adaptation to a new environment can lead to reproductive isolation and speciation, ultimately enabling us to connect barriers to gene flow to adaptive causes of divergence. The pea aphid ( Acyrthosiphon pisum) comprises host races specializing on legume species and provides a unique system for examining the early stages of diversification along a gradient of genetic and associated adaptive divergence. As host choice produces assortative mating, understanding the underlying mechanisms of choice will contribute directly to understanding of speciation. As host choice in the pea aphid is likely mediated by smell and taste, we use capture sequencing and SNP genotyping to test for the role of chemosensory genes in the divergence between eight host plant species across the continuum of differentiation and sampled at multiple locations across western Europe. We show high differentiation of chemosensory loci relative to control loci in a broad set of pea aphid races and localities, using a model‐free approach based on principal component analysis. Olfactory and gustatory receptors form the majority of highly differentiated genes and include loci that were already identified as outliers in a previous study focusing on the three most closely related host races. Consistent indications that chemosensory genes may be good candidates for local adaptation and barriers to gene flow in the pea aphid open the way to further investigations aiming to understand their impact on gene flow and to determine their precise functions in response to host plant metabolites.

On the bioavailability of trace metals in surface sediments: a combined geochemical and biological approach - Stéphanie Roosa; Emilie Prygiel; Ludovic Lesven; Ruddy Wattiez; David Gillan; Benoît J. D. Ferrari; Justine Criquet; Gabriel Billon (Environmental Science and Pollution Research, 2016)

Gene co-expression analysis identifies brain regions and cell types involved in migraine pathophysiology: a GWAS-based study using the Allen Human Brain Atlas - Else Eising; Sjoerd M. H. Huisman; Ahmed Mahfouz; Lisanne S. Vijfhuizen; Verneri Anttila; Bendik S. Winsvold; Tobias Kurth; M. Arfan Ikram; Tobias Freilinger; Jaakko Kaprio; Dorret I. Boomsma; Cornelia M. van Duijn; et al. (Human Genetics, 2016)

Specific global responses to N and Fe nutrition in toxic and non‐toxic Microcystis aeruginosa - Ralitza Alexova; The Cuong Dang; Manabu Fujii; Mark J. Raftery; T. David Waite; Belinda C. Ferrari; Brett A. Neilan (Environmental Microbiology, 2016)
Summary The bloom‐forming cyanobacteria species M icrocystis aeruginosa includes toxic and non‐toxic (microcystin‐producing) strains. Certain stress conditions stimulate synthesis of microcystin ( MCYST ) and enhance the binding of the MCYST molecule to proteins. In this quantitative proteomic study, we compared the response of a wild‐type toxic strain PCC 7806, an mcyH − knockout non‐toxic strain, and a naturally occurring non‐toxic strain, PCC 7005, after 8 days in low iron ( F e) and nitrogen ( N ) starvation in order to assess the benefit of MCYST synthesis in non‐optimal conditions. Fe limitation increased MCYST synthesis and caused an accumulation of phycobilisome proteins and the ferric iron transporter FutA only in the toxic PCC 7806 but not the non‐toxic strains. In N starvation, photosynthetic, C and N metabolism proteins were more abundant in the non‐toxic strains, as were chaperones and proteases. Significant interaction between nutrient availability and toxicity existed for thioredoxin peroxidase and several thioredoxin‐regulated proteins. We propose a competition of MCYST for binding sites in thioredoxin‐regulated proteins during oxidative stress (low F e) but not in growth‐limiting conditions (low N ). This then leads to differences in the regulation of C : N metabolism in toxic and non‐toxic M . aeruginosa in nutrient‐replete and nutrient‐limited conditions.

A unifying gravity framework for dispersal - Eelke Jongejans; Olav Skarpaas; Matthew J. Ferrari; Eric S. Long; Joseph T. Dauer; Carrie M. Schwarz; Emily S. J. Rauschert; Randa Jabbour; David A. Mortensen; Scott A. Isard; David A. Lieb; Zeynep Sezen; et al. (Theoretical Ecology, 2015)

ERp29 deficiency affects sensitivity to apoptosis via impairment of the ATF6–CHOP pathway of stress response - Irina Hirsch; Matthias Weiwad; Erik Prell; David Michael Ferrari (Apoptosis, 2014)

Neuromelanin of the Human Substantia Nigra: An Update - Fabio A. Zucca; Emy Basso; Francesca A. Cupaioli; Emanuele Ferrari; David Sulzer; Luigi Casella; Luigi Zecca (Neurotoxicity Research, 2014)

Iron uptake and toxin synthesis in the bloom‐forming Microcystis aeruginosa under iron limitation - Ralitza Alexova; Manabu Fujii; Debra Birch; Jennifer Cheng; T. David Waite; Belinda C. Ferrari; Brett A. Neilan (Environmental Microbiology, 2011)
Summary Toxin production during cyanobacterial blooms poses a significant public health threat in water bodies globally and requires the development of effective bloom management strategies. Previously, synthesis of the hepatotoxin microcystin has been proposed to be regulated by iron availability, but the contribution of the toxin to the adaptation of cyanobacteria to environmental stresses, such as changing light intensity and nutrient limitation, remains unclear. The aim of this study was to compare the iron stress response in toxic and non‐toxic strains of Microcystis aeruginosa subjected to moderate and severe iron limitation. The transcription of a number of genes involved in iron uptake, oxidative stress response, toxin synthesis and transcriptional control of these processes was accessed by quantitative real‐time PCR (qRT‐PCR). The process of adaptation of M. aeruginosa to iron stress was found to be highly dynamic and strain‐specific. Toxin production in PCC 7806 increased in an iron‐dependent manner and appeared to be regulated by FurA. The inability to produce microcystin, either due to natural mutations in the mcy gene cluster or due to insertional inactivation of mcyH , affected the remodelling of the photosynthetic machinery in iron‐stressed cells, the transport of Fe(II) and transcription of the Fur family of transcriptional regulators. The presence of the toxin appears to give an advantage to microcystin‐producing cyanobacteria in the early stages of exposure to severe iron stress and may protect the cell from reactive oxygen species‐induced damage.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)